2001
DOI: 10.1007/s004310100828
|View full text |Cite
|
Sign up to set email alerts
|

Acute neonatal collapse resulting from pericardial effusion

Abstract: Pericardial effusion should be considered in any baby experiencing acute deterioration with a central venous catheter in place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…A PICC-induced PCE can lead to sudden CT, which has a 75% mortality rate; however, in patients undergoing pericardiocentesis, the mortality decreases to 8% (1), which is close to the mortality (6.25%) among the 24 cases examined. Some researchers have suggested that if infants with PICC have a sudden instability in cardiopulmonary function that cannot be explained by other reasons, emergency pericardiocentesis and drainage should be considered (14). In addition, direct drainage with a PICC can be performed with sudden CT, although the approach may not be successful.…”
Section: Discussionmentioning
confidence: 99%
“…A PICC-induced PCE can lead to sudden CT, which has a 75% mortality rate; however, in patients undergoing pericardiocentesis, the mortality decreases to 8% (1), which is close to the mortality (6.25%) among the 24 cases examined. Some researchers have suggested that if infants with PICC have a sudden instability in cardiopulmonary function that cannot be explained by other reasons, emergency pericardiocentesis and drainage should be considered (14). In addition, direct drainage with a PICC can be performed with sudden CT, although the approach may not be successful.…”
Section: Discussionmentioning
confidence: 99%
“…4 Case study reports of neonates with PCEs document fl uid volume aspirates ranging from 8 to 37 mL. [5][6][7][8] According to Zahka, pericardial tamponade caused by much smaller volumes can occur with rapid accumulation of fl uid. 9 Causes of PCE within the neonatal population include congestive heart failure caused by anemia or myocarditis, neonatal pneumonia, recent cardiac surgery, 9,10 malpositioned CVCs, 4-6,10-15,28 and viral or infl ammatory pericarditis.…”
Section: Etiology and Pathophysiologymentioning
confidence: 98%
“…Sir: In response to the original paper of Drs Bagtharia, Kempley and Hla [1], we would insist that pericardial effusion related to a central venous catheter is not a rare complication of a central line and is a life threatening event.…”
mentioning
confidence: 96%